Improving resource efficiency in the value chain of construction plastics A pathway of service designs enabling increased circularity through mechanical recycling in a Swedish context - Linder, Teodor; Hellqvist, Joar (My University, 2023)
The Swedish construction industry generates more than 150 000 tonnes of plastic waste annually, and only 0.8-2.5 percent of this waste is recycled. A wide variety of plastic types complicates sorting and processing procedures, the low density of plastic materials leads to costly waste transportation, and the project-based nature of the industry implies temporary geographically dispersed plastic waste flows. While these barriers are commonly mentioned in previous research, there are many more reasons behind the low resource efficiency of construction plastic waste. This study was conducted together with the Swedish construction company NCC, to identify circular service opportunities enabling improved resource efficiency of construction plastic waste through mechanical recycling. First, by interviewing people with experience from the construction plastic value chain, six types of services enabling plastic recycling could be found and 113 barriers hindering the provision of these services could be presented in six categories. Further, ideas on how actors can collaborate better to increase the plastic recycling rate were identified through a concept mapping process and could be categorized into eight clusters, representing collaborative actions. Leveraging perspectives of collaboration complexity and service system maturity, eight service system designs were proposed that could enable collaborative actions in practice. A service ecosystem perspective was employed to highlight interdependencies between collaborative actions and suggest a pathway of service designs. Finally, through interviews with digital construction specialists, a knowledge gap was found with respect to how digital solutions could be used to improve plastic waste management. To increase the recycling rate of construction plastic waste, it is suggested that actors consider the proposed service systems to explore solutions with external actors.
Keywords: Construction; Plastic; Service Ecosystems; Circular Economy Business Models; Resource Efficiency Recycling; Service Triads; Reverse Supply Chain; Collaborative Actions; Barriers